Microfocused Ultrasound for Facial Photorejuvenation: A Review - Wulkan, Adam J.; Fabi, Sabrina G.; Green, Jeremy B. (Facial Plastic Surgery, 2016)
Microfocused ultrasound is a unique technology to treat skin laxity of the brow, lower face, and the rhytides of the décolletage. Over the past several years, the efficacy and safety of this device has been well documented and its adoption widespread. By delivering focused acoustic energy, which is converted to heat, this device creates predictable and reproducible microcoagulative zones that initiate a concentrated inflammatory wound response. By targeting the deep reticular dermis and superficial muscle and fascial planes, such as the superficial musculoaponeurotic system, platysma, and pectoralis muscle fascia, this nonablative technology increases neocollagenesis and neoelastogenesis in a novel fashion, while avoiding many of the complications related to epidermal heating observed in several other nonablative devices. Although the results are not equivalent to those of a rhytidectomy, microfocused ultrasound provides an excellent noninvasive means to achieve a regenerative effect on the face, neck, and décolletage when performed in the appropriate patient population.
Keywords: Ulthera; microfocused ultrasound; facial rejuvenation; noninvasive